A Study of the Effect of Multilingual Policy in the Education System on Minority Language Learning - Adawiyah, Rabiyatul (JUPE : Jurnal Pendidikan Mandala, 2025)
This research analyzes the influence of multilingual policies in the Indonesian education system on minority language learning. Using a descriptive-qualitative approach, the study examines the implementation of regulations, learning practices, and the role of schools, families and communities in minority language preservation. Results show that formal policies encourage the preservation of local languages but are faced with resource constraints, the influence of popular culture, and low technological support. Translanguaging practices and integration of multicultural values effectively improve minority language learning. Multisectoral collaboration is important for the sustainability of minority language use in education. The study recommends strengthening policies, improving teacher training and utilizing technology for inclusive and sustainable multilingual education.